2022
DOI: 10.1001/jamaoto.2022.3013
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Issues and Alcohol Consumption in Resident and Fellow Physicians in Otolaryngology Before and During the COVID-19 Pandemic

Abstract: To the Editor We were pleased to read the recent article by Chebib et al. 1 The effects of COVID-19 on resident physician training are not yet fully understood and present a wide range of effects, from issues in educational objectives to mental distress. There is some evidence pointing out that younger and less experienced health professionals, such as resident physicians, are more prone to suffer mental distress when facing unforeseen situations, such as the COVID-19 pandemic. 2 Some studies have shown hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Longitudinal studies with healthcare workers during this pandemic have shown enduring rates of mental distress [ 4 , 15 17 ], although others found a reduction in these frequencies [ 18 ]. We highlight that the consequences related to psychological distress are vast, including increased rates of absenteeism [ 19 ], alcohol misuse, and medical errors [ 20 ], likewise may be related to an unsatisfactory learning experience [ 6 ], which is a keystone in residency training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal studies with healthcare workers during this pandemic have shown enduring rates of mental distress [ 4 , 15 17 ], although others found a reduction in these frequencies [ 18 ]. We highlight that the consequences related to psychological distress are vast, including increased rates of absenteeism [ 19 ], alcohol misuse, and medical errors [ 20 ], likewise may be related to an unsatisfactory learning experience [ 6 ], which is a keystone in residency training.…”
Section: Discussionmentioning
confidence: 99%
“…In the direction of narrow mental distress, psychological and psychiatric assistance should be made available for residents, as well as specific training to improve resilience and incentives towards a healthy lifestyle, including physical exercises [ 19 ]. Additionally, colleagues and staff should be aware of warning signs, such as avoidance behavior, unexplained absenteeism and alcohol abuse [ 20 ]. The training opportunities missed due to the redeployment of residents and faculty members should be addressed by policymakers and supervisors in order to guarantee the proper formation of specialists (profile and number of patients managed by residents, hands-on abilities, professional experience and soft skills).…”
Section: Discussionmentioning
confidence: 99%